Neurobehavioural outcomes in children after In-Hospital cardiac arrest. (March 2018) - Slomine, Beth S.; Silverstein, Faye S.; Christensen, James R.; Holubkov, Richard; Telford, Russell; Dean, J.Michael; Moler, Frank W.; ,
Abstract: Aim: Children who remain comatose after in-hospital cardiac arrest (IH-CA) resuscitation are at risk for poor neurological outcome. We report results of detailed neurobehavioural testing in paediatric IH-CA survivors, initially comatose after return of circulation, and enrolled in THAPCA-IH, a clinical trial that evaluated two targeted temperature management interventions (hypothermia, 33.0 °C or normothermia, 36.8 °C; NCT00880087). Methods: Children, aged 2 days to <18 years, were enrolled in THAPCA-IH from 2009 to 2015; primary trial outcome (survival with favorable neurobehavioural outcome) did not differ between groups. Pre-IH-CA neurobehavioural functioning, measured with the Vineland Adaptive Behavior Scales, Second Edition (VABS-II) was evaluated soon after enrollment; this report includes only children with broadly normal pre-IH-CA scores (VABS-II composite scores ≥70; 269 enrolled). VABS-II was re-administered 3 and 12 months later. Cognitive testing was completed at 12 months. Results: Follow-ups were obtained on 125 of 135 eligible one-year survivors. Seventy-seven percent (96/125) had VABS-II scores ≥70 at 12 months; cognitive composites were ≥2SD of mean in 59%. VABS-II composite, domain, and most subdomain scores declined between pre-IH-CA and 3-month, and pre-IH-CA and 12-month assessments (composite means declined about 1 SD at 3 and 12 months, p < 0.005); 3 and 12-month scores were strongly correlated (r = 0.72, p < 0.001). Conclusions: In paediatric IH-CA survivors at high risk for unfavorable outcomes, the majority demonstrated significant declines in neurobehavioural functioning, across multiple functional domains, with similar functioning at 3 and 12 months. About three-quarters attained VABS-II functional performance composite scores within the broadly normal range.